Urgensi Pengembangan Kebijakan Energi Baru dan Terbarukan Dalam Rangka Ketahanan Energi Nasional - Reny Oktaviani Paturu; Aullia Vivi Yulianingrum (CV Putra Publisher, 2023)
The existence of the use of new energy and renewable energy until now has not been optimal. This study aims to formulate policy concepts for the management and utilization of new and renewable energy in the framework of national energy security. The research method used is normative legal research using a statute approach. The data collection technique uses primary data, namely a number of laws and regulations related to energy and natural resources and secondary data, namely encyclopedias, news in print media, and websites. Then it is analyzed qualitatively, namely legal norms in laws and regulations using deductive thinking logic. The results show that new energy and renewable energy management policies to maintain national energy security need to use legal protection instruments for the interests of private property, common property and state property so that it is necessary to elaborate on the concept of control rights over natural resources by the state regulated in laws and regulations in Indonesia.